2015
DOI: 10.5935/0103-5053.20150126
|View full text |Cite
|
Sign up to set email alerts
|

Maleic Anhydride as a Compatibilizer and Plasticizer in TPS/PLA Blends

Abstract: In recent decades, starch has been studied as a raw material due to low production costs. The limitations associated with starch being highly permeable to water vapor and its mechanical properties being dependent on the relative humidity have been investigated. The proprieties of thermoplastic starch/poly(lactic acid) (TPS/PLA) blends have been studied by researchers, as well as the incorporation of compatibilizers to improve the interfacial interaction between the blend components. The purpose of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…The reason for this phenomenon could be the high viscosity difference of both phases, which will be discussed later. In addition, the weak interface of TPS/PLA blend at 20 wt% of PLA could have an influence on the shape and size of dispersed phase, which can be resolved by further interfacial modification as examined by Shin et al and Clasen et al Also, in the work of Martin and Averous, the similar morphology had been observed for 25 wt% of PLA in TPS matrix . The morphology of 40PLA, 60PLA, and 80PLA samples at the magnification of 500× are shown in Figure B, C, and D, respectively.…”
Section: Resultsmentioning
confidence: 63%
“…The reason for this phenomenon could be the high viscosity difference of both phases, which will be discussed later. In addition, the weak interface of TPS/PLA blend at 20 wt% of PLA could have an influence on the shape and size of dispersed phase, which can be resolved by further interfacial modification as examined by Shin et al and Clasen et al Also, in the work of Martin and Averous, the similar morphology had been observed for 25 wt% of PLA in TPS matrix . The morphology of 40PLA, 60PLA, and 80PLA samples at the magnification of 500× are shown in Figure B, C, and D, respectively.…”
Section: Resultsmentioning
confidence: 63%
“…Good miscibility and degradation were achieved using various alcohols but with reduced mechanical properties due to reaction of the plasticizer with the composite. Also, Clasen et al [19] used maleic anhydride as a plasticizer. An improvement was noticed in the miscibility of the resulting composite, but the mechanical properties were affected.…”
Section: Introductionmentioning
confidence: 99%
“…The moisture loss of the strawberry samples, as well as the increase of moisture in the trays can be related to the water vapor permeability of each package. According to Clasen et al [6], polymers derived from natural sources have high permeability to water vapor compared to the polymers of petrochemical origin. Schmidt and Laurindo [15], in a study to develop packaging from renewable sources based in cassava starch and cellulosic fibers, found that the hygroscopic property of starch-based packaging can be improved by sealing with PVC films.…”
Section: Moisturementioning
confidence: 99%
“…Among the vegetable raw materials used in the production of packaging, starch has received special attention for being an abundant resource, derived from renewable sources, low cost material, it has the potential of complete degradation after use, and the property to form films and foams [3,6,7].…”
Section: Introductionmentioning
confidence: 99%